Kepemimpinan Kepala Sekolah dalam Perencanaan Peningkatan Produktivitas Kinerja Guru di Sekolah Menengah Pertama Swasta Samarinda - Metta Virya Monica; Zaenab Hanim; Yudo Dwiyono (Departement of Mathematics Education, 2023)
This study explores how the principal's leadership in planning to increase teacher performance productivity in Samarinda Private Middle School. This study uses a qualitative approach, data obtained through interviews with school principals and teachers as research informants and observation and documentation, then analyzed using an interactive analysis model. The study results show that the planning carried out by the school principal has been running optimally, and the school principal has developed a plan to improve teacher performance. Planning carried out by the school principal runs systematically, and the teacher feels the assistance of the school principal in improving the quality of learning. Follow-up planning is carried out by noting deficiencies during class observation, calling the teacher concerned personally, and discussing the results through a teacher council meeting. Good school central planning will be able to accelerate teacher performance improvement; this will also have a positive impact on schools and students to get maximum results.